The big catch : a practical introduction to development - Robertson, A. F. (Westview Press, 1995)
The Big Catch is not a book for those who believe in rote learning. Highly regarded as one of the most innovative (and eloquent) anthropologists of 'development,' A. F. Robertson has applied the lessons from the field to the classroom teaching situation. Drawing from his extensive field experience, he has constructed an imaginative case study incorporating documents that are typical of the ones development consultants have to use, and in my experience, have a surprising ring of authenticity. This interactive role-playing case book is an enormously rich and stimulating way of challenging both traditional and nontraditional students to think about the problems of 'development' and how 'development experts' go about trying to alleviate them. It should provide a powerful antidote to those who believe that all that is needed is the right 'attitude.'